Pelatihan Proses Penanganan Tindakan Pertama pada Tempat Kejadian Perkara (TPTKP) pada anggota Satuan Karya Bhayangkara Kwartir Cabang Mandailing Natal - Liantha Adam Nasution (Jurnal Abdi Mas Adzkia, 2022)
ABSTRACT. The crime scene is an important element that cannot be separated from legal events because at the scene of the case there are victims of the perpetrator's crime and evidence used by the perpetrator in committing a crime which will lead to the disclosure of the criminal event that occurred to find out the motives of the perpetrator and find out perpetrators of criminal acts so that they can be held accountable before the law for their actions. The first action at the crime scene (TPTKP) is the basic knowledge to be able to manage the crime scene to facilitate the Police in the Investigation process. The TPTKP training aims to provide theoretical and practical understanding to participants so that they can understand the Criminal and Criminal Procedure Code as well as the Management of Crime Scenes which are targeted at members of the Saka Bhayangkara Kwartir branch of the Natal Mandailing Branch at Krida TPTKP. The method used in this PKM is to provide material on criminal and criminal procedural law and provide simulation practices using scenarios of criminal cases in which there are victims and evidence in the hope that participants can observe and manage the crime scene. The result of this service is that members of the saka Bhayangkara Kwartir branch of the mandailing natal branch can apply the knowledge of Criminal Procedure and Criminal Procedure to legal events and can secure the scene of the case.